In-situ growth ZrC whisker reinforced iron runner castable as well as preparation method and application thereof

By growing ZrC whiskers in situ in the iron groove castable, forming an interactive interspersed network structure, the problem of insufficient service life and oxidation resistance of existing refractory materials under high temperature conditions is solved, and a higher melting point and oxidation resistance temperature is achieved, which significantly improves the high-temperature mechanical properties of the iron groove castable.

CN120172730APending Publication Date: 2025-06-20SHANGHAI UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510516827.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

The high-temperature mechanical properties and high-temperature oxidation resistance of existing refractories cannot meet the various needs of iron groove castables, especially the service life and oxidation resistance of the materials under high temperature conditions are insufficient.

Method used

By growing ZrC whiskers in situ form an interactive interspersed network structure in the matrix and pores of the iron groove castable, the high-temperature mechanical properties and high-temperature oxidation resistance of the iron groove castable are significantly improved.

Benefits of technology

It improves the melting point and oxidation resistance temperature of the iron groove castable, extends the service life of the material, and significantly improves its high-temperature mechanical properties and oxidation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120172730A_ABST
    Figure CN120172730A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of refractory materials, and discloses an in-situ growth ZrC whisker reinforced iron runner castable and a preparation method and application thereof, and the preparation method comprises the following steps: S1, preparing raw materials according to the mass percentage; s2, preparing the whisker reinforced iron runner castable, fully and uniformly mixing ZrC whisker precursor powder, corundum particles and fine powder, silicon carbide particles and fine powder, calcium aluminate cement, spherical asphalt, silicon powder and aluminum powder according to a set proportion, adding water, stirring, and performing prefabrication molding. According to the application of the in-situ growth ZrC whisker reinforced iron runner castable in manufacturing of the blast furnace iron runner, ZrC whiskers grow in situ in a matrix and pores of the iron runner castable when used at a high temperature, and an interlaced network structure is formed in the matrix of the aluminum oxide-silicon carbide-carbon iron runner castable; the high-temperature mechanical property and the high-temperature oxidation resistance of the iron runner castable can be remarkably improved, and the iron runner castable can be widely applied to the technical fields of ultrahigh-temperature metal smelting and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of refractory materials, and specifically relates to an in-situ grown ZrC whisker-reinforced trough castable, a preparation method thereof, and an application thereof. Background Art

[0002] With the development of metal smelting technology and the enlargement of iron-making blast furnaces, higher requirements are put forward for the performance and service life of trough materials due to the increase in hot metal temperature, tapping volume, tapping time, and hot metal flow rate.

[0003] Aluminum oxide-silicon carbide-carbon trough castable does not need to be fired and can be directly used after baking, which greatly reduces the consumption of energy and resources. Moreover, it has excellent resistance to iron slag erosion and thermal conductivity, and is widely used in blast furnace tapping troughs. However, carbon is easy to oxidize. Once the carbon source is oxidized, it will not only reduce the erosion resistance, but also generate more pores, accelerating the penetration of hot metal or molten slag, resulting in a reduction in the service life of the material.

[0004] At present, it has been reported that whiskers can improve the high-temperature mechanical properties and high-temperature oxidation resistance of refractory materials. Patent CN202110025255.3 discloses a silicon carbide whisker and carbon nanotube-reinforced alumina-carbon refractory material and a preparation method thereof. Using elemental silicon powder, carbon powder, and modified thermosetting phenolic resin as whisker growth raw materials, silicon carbide whiskers and carbon nanotubes are in-situ grown under the action of a catalyst to improve the strength and oxidation resistance of the refractory material.

[0005] Patent CN115196983A discloses an in-situ catalytic synthesis of SiCw-reinforced low-carbon alumina-carbon refractory material and a preparation method thereof. Using elemental silicon powder, graphite, and pitch as whisker growth raw materials, SiCw is in-situ catalytically synthesized by adding fluoride to improve the strength of the refractory material. Patent CN114409417A discloses a gate valve slide plate brick for converter slag blocking and a preparation method thereof. By adding an antioxidant containing ZrSiO4 to replace the traditional antioxidants Al and Si, a ZrC phase with higher oxidation resistance and corrosion resistance can be formed by reacting with MgO-C, greatly improving the oxidation resistance of the slide plate brick. Patent CN116573922A discloses a nano-carbon fiber-reinforced low-carbon magnesia-carbon refractory material and a preparation method thereof. Using pitch and thermosetting phenolic resin as whisker growth raw materials and nano-nickel or nano-iron as a catalyst, nano-carbon fibers are in-situ grown to enhance the oxidation resistance, thermal shock stability, and slag erosion resistance of the refractory material.

[0006] However, the melting points, oxidation resistance temperatures, etc. of various whiskers provided by the above-mentioned prior arts still cannot meet the various requirements of trough castable for high-temperature mechanical properties and high-temperature oxidation resistance. Summary of the Invention

[0007] In order to overcome the deficiencies of the above-mentioned existing technologies, the present invention provides an in-situ grown ZrC whisker-reinforced trough castable and its preparation method. Through coordinated improvement of the raw material composition ratio and preparation process, when the trough castable is used at high temperatures, ZrC whiskers grow in-situ in the matrix and pores of the trough castable to form an interpenetrating network structure, so as to significantly improve the high-temperature mechanical properties and high-temperature oxidation resistance of the trough castable, making the melting point and oxidation resistance temperature of the trough castable higher and meeting various requirements of the trough castable.

[0008] In order to achieve the above object, the present invention provides the following technical solutions: A preparation method of an in-situ grown ZrC whisker-reinforced trough castable, characterized in that it includes the following steps: S1. Prepare raw materials according to the mass ratio Large particle size brown fused alumina 15 - 25, particle size 5 - 8 mm; Medium particle size brown fused alumina 10 - 20, particle size 3 - 5 mm; Small particle size brown fused alumina 15 - 20, particle size 1 - 3 mm; Fine powder brown fused alumina 3 - 8, particle size < 1 mm; Small particle size silicon carbide 2 - 8, particle size 1 - 3 mm; Silicon carbide fine powder 5 - 10, particle size < 1 mm; High alumina cement 1 - 4, particle size ≤ 50 nm; Dense fused alumina 3 - 8, particle size ≤ 0.08 mm; α-aluminum oxide 2 - 6, particle size ≤ 100 μm; Activated alumina 2 - 6, particle size ≤ 100 μm; Pitch 1.3 - 5.0, particle size ≤ 2 mm; Aluminum powder 0.2 - 1.0, particle size ≤ 0.074 mm; Silicon powder 0.5 - 1.5, particle size ≤ 0.074 mm; Graphite powder 0.5 - 2, particle size ≤ 0.074 mm; ZrC whisker precursor powder 0.5 - 2, particle size ≤ 200 μm; S2: Prepare the whisker-reinforced trough castable Mix the raw materials in step S1 evenly according to the ratio, then add 1 - 30% water, stir evenly and pour into a mold, and vibrate the mold filled with the material to form a shape; Cure the formed product at room temperature for 24 - 48 h, then dry and solidify it at a temperature of 100 - 130 °C for 10 - 24 h, and finally bake it at 800 °C for 10 - 48 h to obtain a finished product of in-situ grown ZrC whisker-reinforced iron runner castable; During the subsequent high-temperature sintering process of this castable at 1500 °C - 1600 °C, ZrC whiskers grow in-situ in the matrix and pores of the iron runner castable, forming an interpenetrating network structure.

[0009] The ZrC whisker precursor in step S1 is prepared by the following steps: Mix zirconium acetate and water at a mass ratio of 1: (4 - 8) and stir, add 30 - 60 wt% of citric acid based on the mass of zirconium acetate, stir until all the citric acid is dissolved, then add KOH to adjust the pH value of the solution to 6 - 8; Then add a nickel-based catalyst and a whisker growth assistant NaF, and the addition amounts are 0.2 - 0.6 wt% and 1.5 - 2.5 wt% of the total mass of the reaction solution respectively, continuously stir to form a sol, after aging for 24 h, heat and dry to obtain a brown powder, thus obtaining the ZrC whisker precursor.

[0010] The nickel-based catalyst is one or several of nickel nitrate, nickel chloride, nickel sulfate and nickel acetylacetonate, and the average particle size ≥ 100 nm.

[0011] An in-situ grown ZrC whisker-reinforced iron runner castable prepared by the aforementioned method forms an interpenetrating network structure of ZrC whiskers in the matrix of alumina-silicon carbide-carbon iron runner castable under high-temperature service conditions of 1500 °C - 1600 °C.

[0012] An application of the aforementioned in-situ grown ZrC whisker-reinforced iron runner castable in manufacturing the blast furnace iron runner. When the blast furnace iron runner is under high-temperature service conditions of 1500 °C - 1600 °C, ZrC whiskers grow in-situ in the refractory by gas-liquid-solid and gas-solid growth mechanisms. The diameter of the ZrC whiskers is 0.5 μm - 1 μm and the aspect ratio is 10 - 30, forming an interpenetrating network structure in the matrix of alumina-silicon carbide-carbon iron runner castable to improve the high-temperature mechanical properties of the iron runner castable. When the blast furnace iron runner is under high-temperature service conditions of 1500 °C - 1600 °C, specifically, ZrC whiskers are generated in-situ in the pores to fill the pores of the iron runner castable, reduce the porosity, and reduce the diffusion of oxygen into the refractory, so as to improve the high-temperature oxidation resistance of the alumina-silicon carbide-carbon iron runner castable.

[0013] The beneficial effects of the present invention at least include the following points: 1. The present invention provides a method of fully mixing ZrC whisker precursors, corundum particles and fine powders, silicon carbide particles and fine powders, calcium aluminate cement, spherical pitch, silicon powder, and aluminum powder in a set ratio, then adding water and stirring to preform and prepare a trough casting material. When the trough casting material is used at high temperatures, ZrC whiskers grow in-situ in the matrix and pores of the trough casting material, significantly improving the high-temperature mechanical properties and high-temperature oxidation resistance of the trough casting material. Compared with conventional silicon carbide whiskers, the ZrC whisker-reinforced refractory material has the advantages of higher melting point and higher oxidation resistance temperature.

[0014] 2. Specifically, the present invention fully mixes raw materials such as brown corundum granular materials and matrix fine powders (silicon carbide, high-aluminum cement, activated alumina, dense corundum, α-Al2O3) with a set particle size. Using ZrC whisker precursors as the raw materials for preparing ZrC whiskers, under high-temperature use conditions of 1500°C to 1600°C, ZrC whiskers grow in-situ in the refractory material through gas-liquid-solid and gas-solid growth mechanisms, and the obtained ZrC whiskers have a diameter of 0.5 μm to 1 μm and an aspect ratio of 10 to 30.

[0015] 3. Under high-temperature use conditions of 1500°C to 1600°C, the present invention can enable ZrC whiskers to grow in-situ in the matrix of alumina-silicon carbide-carbon trough casting material and form an interpenetrating network structure, significantly improving the high-temperature mechanical properties of the trough casting material. The ZrC whiskers generated in-situ in the pores of the present invention effectively fill the pores of the trough casting material, reduce the porosity, and reduce the diffusion of oxygen into the refractory material, simultaneously improving the high-temperature oxidation resistance of the alumina-silicon carbide-carbon trough casting material.

[0016] 4. The method for preparing an in-situ grown ZrC whisker-reinforced trough casting material of the present invention has a simple process, and the in-situ grown ZrC whiskers are evenly dispersed, which can significantly improve the comprehensive performance of the ZrC whisker-reinforced trough casting material and can be widely applied to technical fields such as ultra-high temperature metal smelting. Description of the Drawings

[0017] Figure 1 SEM image of the trough casting material prepared in Example 1 after high-temperature use, with ZrC whiskers grown in-situ for reinforcement; Figure 2 SEM image of the trough casting material prepared in Example 2 after high-temperature use, with ZrC whiskers grown in-situ for reinforcement; Figure 3 SEM image of the trough casting material prepared in Example 3 after high-temperature use, with ZrC whiskers grown in-situ for reinforcement; Figure 4SEM images of the trough castable prepared in Example 4, the trough castable reinforced by in-situ grown ZrC whiskers after high-temperature use; Figure 5 SEM images of the trough castable prepared in Example 5, the trough castable reinforced by in-situ grown ZrC whiskers after high-temperature use; Figure 6 SEM images of the trough castable prepared in Example 6, the trough castable reinforced by in-situ grown ZrC whiskers after high-temperature use; Figure 7 SEM images of the trough castable prepared in Comparative Example 1, the trough castable after high-temperature use; Figure 8 EDS (line scan) images of the internal ZrC whiskers of the trough castable prepared in Example 5, the trough castable reinforced by in-situ grown ZrC whiskers after high-temperature use; Figure 9 XRD patterns of the trough castable prepared in Example 5, the trough castable reinforced by in-situ grown ZrC whiskers after high-temperature use.

[0018] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. Detailed Embodiments

[0019] The raw materials used in the following embodiments of the present invention are all commercially available. Unless otherwise specified, they are all in mass percentages.

[0020] Basic Embodiment

[0021] The preparation method of the in-situ grown ZrC whisker-reinforced trough castable provided by the embodiment of the present invention includes the following steps: S1. Prepare raw materials according to the mass ratio Large-particle-size brown fused alumina 15 - 25, particle size 5 - 8 mm; Medium-particle-size brown fused alumina 10 - 20, particle size 3 - 5 mm; Small-particle-size brown fused alumina 15 - 20, particle size 1 - 3 mm; Fine-powder brown fused alumina 3 - 8, particle size < 1 mm; Small-particle-size silicon carbide 2 - 8, particle size 1 - 3 mm; Silicon carbide fine powder 5 - 10, particle size < 1 mm; High-alumina cement 1 - 4, particle size ≤ 50 nm; Dense fused alumina 3 - 8, particle size ≤ 0.08 mm; α-aluminum oxide 2 - 6, particle size ≤ 100 μm; Activated alumina 2 - 6, particle size ≤ 100 μm; Pitch 1.3 - 5.0, particle size ≤ 2 mm; Aluminum powder: 0.2 - 1.0, particle size ≤ 0.074 mm; Silicon powder: 0.5 - 1.5, particle size ≤ 0.074 mm; Graphite powder: 0.5 - 2, particle size ≤ 0.074 mm; ZrC whisker precursor powder: 0.5 - 2, particle size ≤ 200 μm; S2: Preparation of whisker-reinforced trough castable Mix the raw materials in step S1 evenly by dry mixing, then add 1 - 15 wt% of water, stir evenly and pour into a mold, and vibrate the mold filled with the material to form; Cure the formed product at room temperature for 24 - 48 h, then dry and solidify at 100 - 130 °C for 10 - 24 h, and finally bake at 800 °C for 10 - 48 h to obtain the finished product of in-situ growth ZrC whisker-reinforced trough castable; During the subsequent high-temperature sintering process at 1500 °C - 1600 °C, ZrC whiskers grow in-situ in the matrix and pores of the trough castable, forming an interpenetrating network structure.

[0022] The ZrC whisker precursor powder in step S1 is prepared by the following steps: Mix zirconium acetate and water at a mass ratio of 1: (4 - 8) and stir, add citric acid accounting for 30 - 60% of the mass of zirconium acetate, stir until all the citric acid is dissolved, then add KOH to adjust the pH value of the solution to 6 - 8; Then add a nickel-based catalyst and a whisker growth aid NaF, and the addition amounts are 0.2 - 0.6 wt% and 1.5 - 2.5 wt% of the total mass of the reaction solution respectively, continuously stir to form a sol, after aging for 24 h, heat and dry to obtain a brown powder, and obtain the ZrC whisker precursor.

[0023] The nickel-based catalyst is one or more of nickel nitrate, nickel chloride, nickel sulfate and nickel acetylacetonate, and the average particle size ≥ 100 nm.

[0024] An in-situ growth ZrC whisker-reinforced trough castable prepared by the foregoing method forms an interpenetrating network structure of ZrC whiskers in the matrix of alumina-silicon carbide-carbon trough castable under high-temperature use conditions of 1500 °C - 1600 °C.

[0025] An application of the foregoing in-situ growth ZrC whisker-reinforced trough castable in manufacturing a blast furnace tapping trough. When the blast furnace tapping trough is under high-temperature use conditions of 1500 °C - 1600 °C, ZrC whiskers grow in-situ in the refractory by gas-liquid-solid and gas-solid growth mechanisms. The diameter of the ZrC whiskers is 0.5 μm - 1 μm and the aspect ratio is 10 - 30, so that the ZrC whiskers form an interpenetrating network structure in the matrix of alumina-silicon carbide-carbon trough castable to improve the high-temperature mechanical properties of the trough castable.

[0026] When the blast furnace runner is under the high-temperature service conditions of 1500°C to 1600°C, ZrC whiskers are in-situ generated in the pores to fill the pores of the runner castable, reduce the porosity, so as to reduce the diffusion of oxygen into the refractory, and improve the high-temperature oxidation resistance of the alumina-silicon carbide-carbon runner castable; during the use (sintering) process of the castable, ZrC whiskers grow in-situ inside the runner castable according to the VLS (vapor-liquid-solid) and VS (vapor-solid) growth mechanisms to form a network, realizing the structural enhancement of the runner castable; and as the use temperature increases, the average length and quantity of the in-situ generated ZrC whiskers also increase slightly, and the network density increases accordingly.

[0027] The following is described in detail with multiple specific examples. In the examples, in the raw materials for preparing the runner castable reinforced by in-situ growing ZrC whiskers, by mass fraction ratio: The large-particle-size brown fused alumina is preferably 18 - 23, most preferably 19 - 21; the medium-particle-size brown fused alumina is preferably 14 - 18, most preferably 15 - 17; the small-particle-size brown fused alumina is preferably 15 - 19, most preferably 16 - 18; the fine-powder brown fused alumina is preferably 4 - 7, most preferably 5 - 6; the small-particle-size silicon carbide is preferably 3 - 7, most preferably 4 - 6; the silicon carbide fine powder is preferably 6 - 9, most preferably 7 - 9%; the high-aluminum cement is preferably 1.3 - 5.5, most preferably 2 - 3; The activated alumina is preferably 1.3 - 5.5, most preferably 2 - 3; the dense fused alumina is preferably 3 - 5.5, most preferably 4 - 5; the α-aluminum oxide is preferably 3 - 5, most preferably 3.5 - 4.5; the pitch is preferably 2 - 3, most preferably 2 - 2.5; the aluminum powder is preferably 0.2 - 1, most preferably 0.6 - 1; the silicon powder is preferably 0.8 - 1.3, most preferably 0.9 - 1.1; the graphite powder is preferably 0.8 - 1.8, most preferably 0.9 - 1.6; the pitch is preferably 1.3 - 5, most preferably 2 - 3; the ZrC whisker precursor is preferably 0.8 - 1.8, most preferably 1.4 - 1.6.

[0028] In each example, the catalyst includes one or several of nickel nitrate, nickel chloride, nickel formate and nickel acetylacetonate, preferably nickel formate, more preferably nickel nitrate; the particle size of the catalyst is ≥100nm, more preferably 200nm ≤ particle size ≤ 2μm, most preferably 300nm ≤ particle size ≤ 500nm; the purity of the catalyst is preferably ≥98%, more preferably 98 - 99.9%, most preferably 99.9%; The particle size of the large-particle-size brown fused alumina is preferably 5 - 8mm, more preferably 5.5 - 7.5mm; The particle size of the medium-particle-size brown fused alumina is preferably 3 - 5mm, more preferably 4.8 - 3.3mm; The particle size of the small particle size brown fused alumina is preferably 1-3 mm, and most preferably 1.5-2.5 mm; The particle size of the fine powder brown fused alumina is preferably <1 mm, more preferably 0.01 mm ≤ particle size ≤ 1 mm, and most preferably 0.05 mm ≤ particle size ≤ 1 mm; The alumina content in the brown fused alumina is preferably ≥93%, and most preferably ≥95%; The particle size of the small particle size silicon carbide is preferably 1.3-2.7 mm, and most preferably 1.5-2.5 mm; The content of the small particle size silicon carbide is preferably ≥93%, and most preferably ≥95%; The particle size of the silicon carbide fine powder is preferably 0.01 mm ≤ particle size ≤ 1 mm, and most preferably 0.1 mm ≤ particle size ≤ 1 mm; The purity of the silicon carbide fine powder is preferably 97-99%, and most preferably 99%; The particle size of the high-alumina cement is preferably 15 nm ≤ particle size ≤ 50 nm, and most preferably 25 nm ≤ particle size ≤ 50 nm; The purity of the high-alumina cement is preferably 97-99%, and most preferably 99%; The particle size of the activated alumina is preferably 0.01 mm ≤ particle size ≤ 0.08 mm, and most preferably 0.03 mm ≤ particle size ≤ 0.07 mm; The purity of the activated alumina is preferably 97-99%, and most preferably 99%; The particle size of the dense fused alumina is preferably 0.01 mm ≤ particle size ≤ 0.08 mm, and most preferably 0.03 mm ≤ particle size ≤ 0.07 mm; The purity of the dense fused alumina is preferably 97-99%, and most preferably 99%; The particle size of the α-alumina is preferably 20 μm ≤ particle size ≤ 100 μm, and most preferably 25 μm ≤ particle size ≤ 70 μm; The purity of the α-alumina is 97-99%, and most preferably 99%; The particle size of the aluminum powder is preferably 0.015 mm ≤ particle size ≤ 0.074 mm, and most preferably 0.03 mm ≤ particle size ≤ 0.074 mm; The purity of the aluminum powder is preferably 97-99%, and most preferably 99%; The particle size of the graphite powder is preferably 0.01 mm ≤ particle size ≤ 0.074 mm, and most preferably 0.03 mm ≤ particle size ≤ 0.074 mm; The purity of the graphite powder is preferably 98-99%, and most preferably 99%; The particle size of the asphalt is preferably 0.01 mm ≤ particle size ≤ 1 mm, and most preferably 0.05 mm ≤ particle size ≤ 1 mm; The particle size of the silicon powder is preferably 0.02 mm ≤ particle size ≤ 0.074 mm, and most preferably 0.03 mm ≤ particle size ≤ 0.06 mm; The purity of the silicon powder is preferably 2N - 3N, and most preferably 3N; In the present invention, the raw materials are first dry - mixed according to the formula, and then an appropriate amount of water is added and stirred until homogeneous. In the present invention, the time for dry - mixing is preferably 60 - 90 min, and most preferably 80 min; The time for adding water and stirring is preferably 6 - 10 min, and most preferably 10 min; The vibration frequency is preferably greater than 2860 times / minute, and most preferably 2900 times / minute; the vibration amplitude is preferably 0.55 mm, and most preferably 0.5 mm; the vibration time is preferably 10 - 30 min, and most preferably 20 min; The curing temperature is preferably 20 - 30 °C, and most preferably 25 °C; the curing time is preferably 30 - 45 h, and most preferably 36 h; The drying temperature is preferably 105 - 120 °C, and most preferably 110 °C; the drying time is preferably 15 - 24 h, and most preferably 24 h; The inert gas is preferably argon and nitrogen, and most preferably argon; the sintering temperature is preferably 1400 - 1600 °C, more preferably 1450 - 1550 °C, and most preferably 1500 °C; the sintering time is preferably 2.3 - 5.5 h, and most preferably 3 h.

[0029] Example 1 The in - situ growth ZrC whisker - reinforced trough castable, its preparation method and application provided in this example are specific selections based on the above - mentioned basic example. The differences are as follows: In this example, by mass, the raw materials for preparing the in - situ growth ZrC whisker - reinforced trough castable are: large - particle size brown fused alumina 15, medium - particle size brown fused alumina 10, small - particle size brown fused alumina 15, fine - powder brown fused alumina 3, small - particle size silicon carbide 2, silicon carbide fine powder 5, high - alumina cement 1, dense fused alumina 4.5, α - type alumina 4, activated alumina 3, pitch 2.5, aluminum powder 1, silicon powder 1, graphite powder 1.5, and whisker precursor powder 1; The ZrC whisker precursor in step S1 is prepared by the following steps: Mix zirconium acetate and water at a mass ratio of 1:4 and stir. Add citric acid accounting for 30wt% of the mass of zirconium acetate. After stirring until all the citric acid is dissolved, add KOH to adjust the pH value of the solution to 6-7. Then add a nickel-based catalyst (nickel nitrate, average particle size ≥100nm) and a whisker growth aid NaF, and the addition amounts are 0.2wt% and 1.5wt% of the total mass of the reaction solution respectively. Continuously stir to form a sol. After aging for 24h, heat and dry to obtain a brownish powder, and obtain the ZrC whisker precursor powder.

[0030] A method for preparing an in-situ grown ZrC whisker-reinforced trough castable, the steps are as follows: Dry mix the raw materials according to the ratio with a mixer for 60min, then add 5wt% of water additionally. After stirring evenly, pour it into a mold. After the mold filled with the material is vibrationally formed, cure it at room temperature for 24h, then dry and solidify it at 130°C for 10h, and finally bake it at 800°C for 10h to obtain the ZrC whisker-reinforced trough castable.

[0031] When the trough castable is used under the condition of 1400°C, the high-temperature condition enables the ZrC whiskers to grow in-situ in the refractory material by the gas-liquid-solid and gas-solid growth mechanisms, forming a large number of intertwined fine rod-shaped networks. The diameter of the ZrC whiskers is concentrated in the range of 0.5μm - 1μm, and the aspect ratio is 10 - 30. Its SEM image is as Figure 1 shown. From Figure 1 it can be seen that the rod-shaped ZrC whiskers form an interpenetrating network structure in the matrix of the alumina-silicon carbide-carbon trough castable, which can significantly improve the high-temperature mechanical properties of the trough castable.

[0032] Example 2 The in-situ grown ZrC whisker-reinforced trough castable, preparation method and its application provided in this example are specific selections based on the above basic example. The differences from Example 1 are as follows: In this example, by mass, the raw materials for preparing the in-situ grown ZrC whisker-reinforced trough castable are: By mass, the raw materials for preparing the in-situ grown ZrC whisker-reinforced trough castable are: 25 large-particle-size brown fused alumina, 20 medium-particle-size brown fused alumina, 20 small-particle-size brown fused alumina, 8 fine-particle-size brown fused alumina, 8 small-particle-size silicon carbide, 10 silicon carbide fine powder, 4 high-aluminum cement, 4.5 dense corundum, 4 α-aluminum oxide, 3 activated alumina, 2.5 asphalt, 1 aluminum powder, 1 silicon powder, 1.5 graphite powder, and 1.5 whisker precursor powder.

[0033] The ZrC whisker precursor among them is prepared by the following steps: Mix zirconium acetate and water at a mass ratio of 1:5 and stir. Add citric acid accounting for 40 wt% of the mass of zirconium acetate. Stir until all the citric acid is dissolved, then add KOH to adjust the pH value of the solution to 7-8. Then add a nickel-based catalyst (nickel chloride) and a whisker growth aid NaF, and the addition amounts are 0.3 wt% and 2 wt% of the total mass of the reaction solution respectively. Continuously stir to form a sol. After aging for 24 h, heat and dry to obtain a brownish powder, and obtain a ZrC whisker precursor.

[0034] A preparation method of in-situ grown ZrC whisker-reinforced iron runner castable, the steps are as follows: Dry mix the raw materials according to the ratio with a mixer for 60 min, then add 5 wt% of water additionally. After stirring evenly, pour it into a mold; vibrate and mold the mold filled with the material, cure it at room temperature for 24 h, then dry and solidify it at 130 °C for 10 h, and finally bake it at 800 °C for 10 h to be usable; When this iron runner castable is used under the condition of 1500 °C, the high-temperature condition enables the ZrC whiskers to grow in-situ in the refractory material by the gas-liquid-solid and gas-solid growth mechanisms, forming a large number of intertwined fine rod-shaped networks. The diameter of the ZrC whiskers is concentrated in 0.5 μm - 1 μm, and the aspect ratio is 10 - 30. Its SEM image is as Figure 2 shown. From Figure 2 it can be seen that the rod-shaped ZrC whiskers form an interpenetrating network structure in the matrix of the alumina-silicon carbide-carbon iron runner castable. The average length and total quantity are slightly increased compared with Example 1, and it can significantly improve the high-temperature mechanical properties of the iron runner castable.

[0035] Example 3 The in-situ grown ZrC whisker-reinforced iron runner castable, preparation method and its application provided in this example are specific selections based on the above basic example. The difference from Example 2 is that: In this example, by mass, the raw materials for preparing the in-situ grown ZrC whisker-reinforced iron runner castable are: large particle size brown fused alumina 20, medium particle size brown fused alumina 16, small particle size brown fused alumina 17, fine powder brown fused alumina 5, small particle size silicon carbide 5, silicon carbide fine powder 8, high alumina cement 2.5, dense fused alumina 3, α-alumina 2, activated alumina 2, pitch 1.3, aluminum powder 0.2, silicon powder 0.5, graphite powder 0.5 and whisker precursor powder 1.75.

[0036] The ZrC whisker precursor powder therein is prepared by the following steps: Mix zirconium acetate and water at a mass ratio of 1:6 and stir. Add citric acid accounting for 50 wt% of the mass of zirconium acetate. After stirring until all the citric acid is dissolved, add KOH to adjust the pH value of the solution to 6-7. Then add a nickel-based catalyst (nickel sulfate) and a whisker growth aid NaF, and the addition amounts are 0.4 wt% and 2.1 wt% of the total mass of the reaction solution respectively. Continuously stir to form a sol. After aging for 24 h, heat and dry to obtain a brownish powder, and obtain a ZrC whisker precursor.

[0037] A preparation method of in-situ grown ZrC whisker-reinforced trough castable, the steps are as follows: Dry mix the raw materials according to the ratio with a mixer for 60 min, then add an additional 5 wt% of water. After stirring evenly, pour it into a mold. After the mold filled with the material is vibrationally formed, cure it at room temperature for 24 h, then dry and solidify it at 130 °C for 10 h, and finally bake it at 800 °C for 10 h to be usable.

[0038] When this trough castable is used under the condition of 1600 °C, the high-temperature condition enables the ZrC whiskers to grow in-situ in the refractory material by the gas-liquid-solid and gas-solid growth mechanisms, forming a large number of intertwined fine rod-shaped networks. The diameter of the ZrC whiskers is concentrated in 0.5 μm - 1 μm, and the aspect ratio is 10 - 30. The average length and the total number are increased compared with those in Examples 1 - 2, and most reach or exceed 8 μm. Its SEM diagram is as Figure 3 shown. From Figure 3 it can be seen that numerous rod-shaped ZrC whiskers with different lengths and intertwined with each other form an interpenetrating and tight network structure in the matrix of the alumina-silicon carbide-carbon trough castable, which can significantly improve the high-temperature mechanical properties of the trough castable.

[0039] Example 4 The in-situ grown ZrC whisker-reinforced trough castable, its preparation method and application provided in this example are specific selections based on the above basic examples. The difference from Example 2 is that: Calculated by mass parts, the preparation raw materials of the in-situ grown ZrC whisker-reinforced trough castable are: 20 large-particle brown fused alumina, 16 medium-particle brown fused alumina, 17 small-particle brown fused alumina, 5 fine-particle brown fused alumina, 5 small-particle silicon carbide, 8 silicon carbide fine powder, 2.5 high-aluminum cement, 8 dense fused alumina, 6 α-aluminum oxide, 6 activated alumina, 5 asphalt, 1 aluminum powder, 1.5 silicon powder, 2 graphite powder and 0.5 whisker precursor powder.

[0040] Among them, the ZrC whisker precursor is prepared by the following steps: Mix zirconium acetate and water at a mass ratio of 1:7 and stir. Add citric acid accounting for 60 wt% of the mass of zirconium acetate. After stirring until all the citric acid is dissolved, add KOH to adjust the pH value of the solution to 6 - 7. Then add a nickel-based catalyst (nickel acetylacetonate) and a whisker growth assistant NaF, and the addition amounts are 0.5 wt% and 2.25 wt% of the total mass of the reaction solution respectively. Continuously stir to form a sol. After aging for 24 h, heat and dry to obtain a brownish powder, thus obtaining a ZrC whisker precursor.

[0041] When this trough castable is used under the condition of 1500 °C, the high-temperature condition enables the ZrC whiskers to grow in-situ in the refractory material by the gas-liquid-solid and gas-solid growth mechanisms, forming a large number of intertwined fine rod-like networks. The diameter of the ZrC whiskers is concentrated in the range of 0.5 μm - 1 μm, and the aspect ratio is 10 - 30. The total quantity is slightly less than that in Examples 1 - 2, and most reach or exceed 8 μm. Its SEM image is as Figure 4 shown. From Figure 4 it can be seen that numerous rod-like ZrC whiskers with different lengths and intertwined with each other form an interpenetrating and tight network structure in the matrix of the alumina-silicon carbide-carbon trough castable, which can significantly improve the high-temperature mechanical properties of the trough castable.

[0042] Example 5 The in-situ growth ZrC whisker-reinforced trough castable, its preparation method and application provided in this example are specific selections based on the above basic example. The difference from Example 2 is as follows: In terms of parts by mass, the raw materials for preparing the in-situ growth ZrC whisker-reinforced trough castable are: 20 parts of large-sized brown fused alumina, 16 parts of medium-sized brown fused alumina, 17 parts of small-sized brown fused alumina, 5 parts of fine powder brown fused alumina, 5 parts of small-sized silicon carbide, 8 parts of silicon carbide fine powder, 2.5 parts of high-aluminum cement, 4.5 parts of dense corundum, 4 parts of α-aluminum oxide, 3 parts of activated alumina, 2.5 parts of pitch, 0.5 part of aluminum powder, 1 part of silicon powder, 1.5 parts of graphite powder, and 1.5 parts of whisker precursor powder.

[0043] The ZrC whisker precursor among them is prepared by the following steps: Mix zirconium acetate and water at a mass ratio of 1:8 and stir. Add citric acid accounting for 50 wt% of the mass of zirconium acetate. After stirring until all the citric acid is dissolved, add KOH to adjust the pH value of the solution to 7 - 8. Then add a nickel-based catalyst (nickel acetylacetonate) and a whisker growth assistant NaF, and the addition amounts are 0.6 wt% and 2.5 wt% of the total mass of the reaction solution respectively. Continuously stir to form a sol. After aging for 24 h, heat and dry to obtain a brownish powder, thus obtaining a ZrC whisker precursor.

[0044] When this trough castable is used under the condition of 1500 °C, the high-temperature condition enables ZrC whiskers to grow in situ in the refractory material by the gas-liquid-solid and gas-solid growth mechanisms, forming a large number of intertwined fine rod-like networks. The diameter of the ZrC whiskers is concentrated in the range of 0.5 μm to 1 μm, and the aspect ratio is 10 to 30. The total quantity has increased compared with those in Examples 1-4, and some of them are longer, reaching or exceeding 10 μm. Its SEM image is as shown in Figure 5 shown. It can be seen from Figure 5 that there are numerous rod-like ZrC whiskers with different lengths and intertwined with each other. The number of longer whiskers has increased, forming a more tightly intertwined network structure in the matrix of the alumina-silicon carbide-carbon trough castable, which can significantly improve the high-temperature mechanical properties of the trough castable.

[0045] Figure 8 is the EDS (line scan) image of the internal ZrC whiskers of the trough castable prepared in this example, which is enhanced by in-situ grown ZrC whiskers after high-temperature use; Figure 9 is the XRD pattern of the trough castable prepared in this example, which is enhanced by in-situ grown ZrC whiskers after high-temperature use. Both figures show that there are a large number of in-situ grown ZrC whiskers after high-temperature use, and the comprehensive strength of the trough castable is significantly enhanced.

[0046] Example 6 The in-situ grown ZrC whisker-reinforced trough castable, preparation method and application provided in this example are specific selections based on the above basic examples. The difference from Example 2 is that: In terms of mass parts, the preparation raw materials of the in-situ grown ZrC whisker-reinforced trough castable are: 20 of large-sized brown fused alumina, 16 of medium-sized brown fused alumina, 17 of small-sized brown fused alumina, 5 of fine-powder brown fused alumina, 5 of small-sized silicon carbide, 8 of silicon carbide fine powder, 2.5 of high-aluminum cement, 4.5 of dense fused alumina, 5 of α-aluminum oxide, 4 of activated alumina, 3.5 of pitch, 1 of aluminum powder, 1 of silicon powder, 1.5 of graphite powder and 2.0 of whisker precursor powder.

[0047] The ZrC whisker precursor therein is prepared by the following steps: Mix zirconium acetate and water at a mass ratio of 1:8 and stir. Add citric acid accounting for 50 wt% of the mass of zirconium acetate, and stir until all the citric acid is dissolved. Then add KOH to adjust the pH value of the solution to 6; then add a nickel-based catalyst and a whisker growth aid NaF, and the addition amounts are 0.25 wt% and 1.75 wt% of the total mass of the reaction solution respectively. Keep stirring to form a sol, and after aging for 24 h, heat and dry to obtain a brown powder, thus obtaining the ZrC whisker precursor.

[0048] When this trough castable is used at 1500 °C, the high-temperature condition enables ZrC whiskers to grow in-situ in the refractory by gas-liquid-solid and gas-solid growth mechanisms, forming a large number of intertwined fine rod-shaped networks. The diameter of the ZrC whiskers is concentrated in the range of 0.5 μm to 1 μm, and the aspect ratio is 10 to 30. The total quantity has increased compared to Examples 1-5. Its SEM image is as shown in Figure 5 shown. It can be seen from Figure 5 that there are numerous rod-shaped ZrC whiskers of different lengths and intertwined with each other. With a larger number of whiskers, a more tightly intertwined network structure is formed in the matrix of the alumina-silicon carbide-carbon trough castable, which can significantly improve the high-temperature mechanical properties of the trough castable.

[0049] Comparative Example 1 The trough castable, preparation method and its application provided by the comparative example are basically the same as the components, ratios, preparation methods, experimental steps, etc. of Example 2 above. The difference is that the mass fraction of the added whisker precursor powder is 0 (not added).

[0050] When this trough castable is used at 1500 °C, no network structure formed by in-situ growth of ZrC whiskers is found in the refractory, and there is no connection substance or structure in the pores between the particles of each material. Its SEM image is as shown in Figure 7 shown.

[0051] The in-situ grown ZrC whisker-reinforced trough castables prepared in Examples 1-6 and Comparative Example 1 are tested for room-temperature compressive strength, room-temperature flexural strength, high-temperature flexural strength and oxidation resistance. Among them, the room-temperature compressive strength test of the refractory is carried out according to the standard test method of GB / T 5072-2008, and the room-temperature flexural strength test of the refractory is carried out according to the standard test method of GB / T 3001-2007. The above two tests are carried out on a YAW300D compressive and flexural testing machine. The high-temperature flexural strength test of the refractory is carried out according to the standard test method of GBT3002-2017. The high-temperature oxidation resistance test of the sample is carried out in a tube furnace with an open mouth diameter of φ80. The oxidation test temperature is 1500 °C, the heating rate is 5 °C / min, and the oxidation test time is 2 h. The test results are shown in Table 1 and Table 2.

[0052] Table 1

[0053] Table 2

[0054] In the above embodiments of the present invention, the key is to fully mix ZrC whisker precursor powder, corundum particles and fine powder, silicon carbide particles and fine powder, calcium aluminate cement, spherical pitch, silicon powder, and aluminum powder in a certain proportion, and then add water and stir to pre-form and prepare a trough castable. When the trough castable is used at high temperature, ZrC whiskers grow in-situ in the matrix and pores of the trough castable to form a dense intertwined network, so as to significantly improve the high-temperature mechanical properties and high-temperature oxidation resistance of the trough castable.

[0055] It should be particularly noted that within the scope of the components, ratios, and process parameters described in the present invention, selecting other components, ratios, and process parameters can also achieve the technical effects of the present invention. Therefore, the present invention will not list them one by one.

[0056] Although the above embodiments have described the present invention in detail, they are only a part of the embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on these embodiments without creative efforts, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing an in-situ grown ZrC whisker reinforced iron channel castable, characterized in that: It includes the following steps: S1. Prepare raw materials according to mass ratio Large particle size brown corundum 15~25, particle size 5~8mm; Medium particle size brown corundum 10~20, particle size 3~5mm; Small particle size brown corundum 15~20, particle size 1~3mm; Fine powder brown corundum 3~8, particle size <1mm; Small particle size silicon carbide 2~8, particle size 1~3mm; Silicon carbide fine powder 5~10, particle size <1mm; High alumina cement 1~4, particle size ≤50 nm; Dense corundum 3~8, particle size ≤0.08 mm; α-alumina 2~6, particle size ≤100μm; Activated alumina 2~6, particle size ≤100μm; Asphalt 1.3~5.0, particle size ≤2mm; Aluminum powder 0.2~1.0, particle size ≤0.074mm; Silica powder 0.5~1.5, particle size ≤0.074mm; Graphite powder 0.5~2, particle size ≤0.074mm; ZrC whisker precursor powder 0.5~2, particle size ≤200μm; S2: Preparation of whisker-reinforced iron trough castable The raw materials in step S1 are dry-mixed evenly according to a proportion, and then 1-15 wt % of water is added, stirred evenly, and poured into a mold, and the mold filled with the material is vibrated to form; the molded product is cured at room temperature for 24-48 hours, and then dried and cured at 100-130° C. for 10-24 hours, and finally baked at 800° C. for 10-48 hours to obtain an in-situ grown ZrC whisker reinforced iron ditch castable finished product; during the subsequent high-temperature sintering process of 1500° C. to 1600° C. of the castable finished product, ZrC whiskers grow in-situ in the matrix and pores of the iron ditch castable to form an interlaced network structure.

2. The method for preparing the in-situ grown ZrC whisker reinforced iron channel castable according to claim 1, characterized in that: The ZrC whisker precursor powder in step S1 is prepared by the following steps: Zirconium acetate and water are mixed and stirred in a mass ratio of 1: (4-8), citric acid is added at 30-60wt% of the mass of zirconium acetate, and the mixture is stirred until the citric acid is completely dissolved. KOH is added to adjust the pH value of the solution to 6-8. A nickel-based catalyst and a whisker growth promoter NaF are then added in amounts of 0.2-0.6wt% and 1.5-2.5wt% of the total mass of the reaction solution, respectively. The mixture is stirred continuously to form a sol, and after aging for 24 hours, a brown powder is obtained by heating and drying to obtain a ZrC whisker precursor powder.

3. The method for preparing the in-situ grown ZrC whisker reinforced iron channel castable according to claim 2, characterized in that: The nickel-based catalyst is one or more of nickel nitrate, nickel chloride, nickel sulfate and nickel acetylacetonate, and has an average particle size of ≥100 nm.

4. An in-situ grown ZrC whisker reinforced iron channel castable prepared by the method according to any one of claims 1 to 3, wherein under high temperature use conditions of 1500°C to 1600°C, the ZrC whiskers form an interlaced network structure in the matrix of the alumina-silicon carbide-carbon iron channel castable.

5. Use of the in-situ grown ZrC whisker reinforced iron ditch castable according to claim 4 in manufacturing the iron ditch of a blast furnace.

6. The use according to claim 5, characterized in that: When the blast furnace iron channel prepared by the method is used at a high temperature of 1500°C to 1600°C, ZrC whiskers are grown in situ in the refractory material by gas-liquid-solid and gas-solid growth mechanisms. The ZrC whiskers have a diameter of 0.5 μm to 1 μm and an aspect ratio of 10 to 30, and form a network structure that interpenetrates in the matrix of alumina-silicon carbide-carbon iron channel castables to improve the high-temperature mechanical properties of the iron channel castables.

7. The use according to claim 5, characterized in that: When the blast furnace iron channel is used under high temperature conditions of 1500°C to 1600°C, ZrC whiskers are generated in situ in the pores to fill the pores of the iron channel castable, reduce the porosity, and reduce the diffusion of oxygen into the refractory material, so as to improve the high temperature oxidation resistance of the alumina-silicon carbide-carbon iron channel castable.

Citation Information

Patent Citations

  • A whisker-reinforced lightweight alumina-carbon refractory material and its preparation method

    CN112811917B

  • Gate valve sliding plate brick for converter slag stopping and preparation method of gate valve sliding plate brick

    CN114409417A

  • In-situ catalytic synthesis SiCw reinforced low-carbon aluminum-carbon refractory material and preparation method thereof

    CN115196983A

  • Carbon nanofiber reinforced low-carbon magnesia carbon refractory material and preparation method thereof

    CN116573922A